Impact of some deacidification means on the changes of selected properties of pulp - Hájek, Matěj; Milichovský, Miloslav; Filipi, Michaela; Mikala, Ondřej (Trans Tech Publications, 2016)
Deacidification is one of the basic restoration techniques to protect archival records stored in various depositories. This study examines the influence of selected deacidification means on lignocellulose materials. Samples represent the commonly used pulps in the paper industry. These materials treated with three deacidification means in cooperation with National Archive in Prague. We monitored for changes as the optical, mechanical and chemical properties and changes on hypermolecular level.
Vliv některých odkyselujících prostředků na vybrané vlastnosti buničin
Keywords: deacidification; lignocellulose materials; hypermolecular properties; odkyselení; lignocelulózové materiály; hypermolekulární vlastnosti